2018
DOI: 10.3389/fmicb.2018.00503
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of the Function and Maintenance of Sexual Reproduction in Dikaryotic Fungi

Abstract: Sexual reproduction likely evolved as protection from environmental stresses, specifically, to repair DNA damage, often via homologous recombination. In higher eukaryotes, meiosis and the production of gametes with allelic combinations different from parental type provides the side effect of increased genetic variation. In fungi it appears that while the maintenance of meiosis is paramount for success, outcrossing is not a driving force. In the subkingdom Dikarya, fungal members are characterized by existence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 155 publications
1
45
0
Order By: Relevance
“…Recently it has been suggested that the maintenance of mating type genes in dikaryotic fungi could have more profound meaning in multiple aspects of life style than just regulating sexual reproduction (33). Given the crucial functions and lack of understanding of these mating type genes in wheat rust fungi, we investigated the mating type genes across the phased genomes of the three Pt isolates.…”
Section: Identification Of Mating Type Genes In the Three Pt Isolatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently it has been suggested that the maintenance of mating type genes in dikaryotic fungi could have more profound meaning in multiple aspects of life style than just regulating sexual reproduction (33). Given the crucial functions and lack of understanding of these mating type genes in wheat rust fungi, we investigated the mating type genes across the phased genomes of the three Pt isolates.…”
Section: Identification Of Mating Type Genes In the Three Pt Isolatesmentioning
confidence: 99%
“…One possible explanation could be that such a high diversity may be necessary for the successful heterodimerization of the HD genes in the SH process, which generates active transcription factors leading to a new developmental pathway (37). This pathway may involve biological processes crucial for a successful SH, such as DNA damage repair via homologous recombination, which has been suggested as the most plausible reason for maintaining the mating type genes in dikaryotic fungi without sexual reproduction (33).…”
Section: High Diversity Within Specificity Region At B Loci Is Associmentioning
confidence: 99%
“…The dikaryotic fungi (Ascomycetes and Basidiomycetes) include some of the most well-studied microbial eukaryotic species with respect to sexual reproduction. Wallen and Perlin [76] concluded in a 2018 review of the function and maintenance of sexual reproduction in the dikaryotic fungi that sexual reproduction, including its central feature of homologous recombination, evolved to repair DNA damages that arise particularly from environmental stresses. In the ascomycete yeast S. cerevisiae, DNA repair by homologous recombination during mitosis is well established.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, in their respective hosts, each variety is able to resist the plants' attempts to eliminate infection, while, in the other species, the fungus succumbs to the plant's defense mechanisms. This selection phenomenon, probably does not favor variation within the mating type locus to reduce promiscuity between different species, though some studies sustain that it favors the maintenance of other specific genes that allow proliferation within the host, despite the plants' attempts to eliminate infection (Wallen and Perlin, 2018).…”
Section: Discussionmentioning
confidence: 99%